Q: 2x plus 2x plus 2x equals 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

6 + 2x = 5x + 9 , 6 - 9 = 5x - 2x , -3 = 3x , x = -1

2x + 4 = 10 2x = 10 - 4 = 6 2x = 6 x = 6/2 = 3

2x + 7 = 1 Therefore, 2x = -6 x = -6/2 x = -3

2x+4 = -16 2x = -16-4 2x = -20 x = -10

6 2(6) + 3 = 9

Related questions

8x-7 plus 2x equals 6 plus 5x plus 2?

-2x-6= -2x-6Another answer:-2x-6 = 2x+6-2x-2x = 6+6-4x = 12x = -3

2x-11

5 - 2x = 8 x = -1 and 1/2 4x = 6 x = 6/4 or 3/2

4x+35-2x+25 = 6 2x+60 = 6 2x = 6-60 2x = -54 x = -27

6y

2x+2=x+6 first subtract 2x. -2x -2x2=-1x+6 then subtract 6-6 -6-4=-1x finally divide by -1x=4 X equals four.

DIE

6 + 2x = 5x + 9 , 6 - 9 = 5x - 2x , -3 = 3x , x = -1

22+2x = 37+6+x 2x-x = 37+6-22 x = 21

2x + 1 = 6 2x = 5 x = 5/2 or 2.5

if: 2x + 6 = -6 then: 2x = -12 x = -6 if: 5x + 7y = 1 then: 5(-6) + 7y = 1 7y = 31 y = 31/7